(untitled) (Ágora UNLaR, 2023)
Jacobinos sin revolución II es una obra colectiva resultado de las actividades de docencia e investigación de su compilador el Dr. Adrián Mercado Reynoso. La propuesta se sitúa en el campo de estudios sobre la historia argentina contemporánea y se propone indagar, desde un enfoque histórico social – local, la radicalización política en torno a la segunda mitad siglo XX y las movilizaciones ecológicas de principios del siglo XXI que protagonizaron diversos sectores sociales de la provincia de La Rioja. Review of Jacobinos sin revolución II Historical memory and local memory during the years of political violence in contemporary Argentina Adrián Mercado Reynoso (comp.) Abstract Jacobins without Revolution II is a collective work resulting from the teaching and research activities of its compiler, Dr. Adrián Mercado Reynoso. The proposal is located in the field of studies on contemporary Argentine history and intends to investigate, from a social-local historical approach, the political radicalization around the second half of the 20th century and the ecological mobilizations of the beginning of the 21st century that led various social sectors of the province of La Rioja. Keywords: La Rioja, OPM, Ecology